INVESTASI SWASTA SEKTOR PARIWISATA DAN PENYERAPAN TENAGA KERJA DI PROVINSI BALI (Sebuah Analisis Tipologi Daerah) - Setyadhi Mustika, Made Dwi (INPUT Jurnal Ekonomi dan Sosial, 2009)
This paper discuss about private invesment of tourism sector and labour absorbtion in Bali Province for the year2002-2005, which is analysed using tipologi area. The data used are secondary data, consisted of private invesmenton tourism sector and labour absorbtion in 9 (nine) regencies/city in Bali Province. The data obtained fromBKPMD of Bali Province, Labour Office of Bali Province, and BPS of Bali Province.The result of the research could be elaborated as follows. Badung Regency, Karangasem Regency, and DenpasarCity are owning private invesment of tourism sector and labour absorbtion level higher than mean of BaliProvince. Jembrana Regency and Bangli Regency are owning private invesment of tourism sector and labourabsorbtion level lower than mean of Bali Province.